Integrated Sustainable Urban Development Strategies towards territorial cohesion: the Portuguese Case - Medeiros, E. (#EURegionsWeekUniversity – Are Integrated Sustainable Urban Development Strategies contributing to a more cohesive EU territory? - 13WS21366, 2021)
This workshop debated the contribution of EU Integrated Strategies for Sustainable Urban Development (SUDs) to promoting sustainable and inclusive urbanisation in three EU Member States (Portugal, Poland and Finland) and a complementary analysis of an urban integrated strategy and subregional planning process in Central America. The presenters concluded that the EU SUDs have had an important impact on promoting a more cohesive EU by helping fund projects which support: (I) environmental sustainability processes in several domains; (ii) social cohesion via the physical and social rehabilitation of deprived urban neighbourhoods and specific buildings, and (iii) territorial governance and cooperation processes via the engagement of multi-level governance, metropolitan collaboration and shared strategy-shared leadership. Likewise, a regional integration perspective has the potential to increase the coordination of urban planning responses in Central American cities.